Bank Specific Factors and Bank Performance: Evidence from Nigeria - Ebenezer Mayowa Ariyibi; Lateef Adewale Yunusa; Tolulope Oyakhilome Williams (Signifikan: Jurnal Ilmu Ekonomi, 2020)
The impact of bank-specific factors on the performance of the deposit money banks in a country has been an area of inquiry for any bank-based financial system. The research investigates the impacts of bank-specific factors on bank performance in Nigeria within 2014-2018. This research use panel data from ten banks that had the best deposit in 2018. The panel data approach found a significant negative relationship between asset quality and return on asset and a significant positive relationship between loan-to-deposit ratio, capital adequacy, and return on asset. In this regard, strategic management should ensure chasing their functional intermediation role and ensure liquidity preference to meet its day-to-day obligations.JEL Classification: G21, G32, C33 How to Cite:Ariyibi, E. M., Yunusa, L. A., & Williams, T. O. (2020). Bank Specific Factors and Bank Performance: Evidence from Nigeria. Signifikan: Jurnal Ilmu Ekonomi, 9(2), 167-176. https://doi.org/10.15408/sjie.v9i2.14658.